2017
DOI: 10.1002/ajoc.201600576
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lewis Acids on Photoredox Catalysis

Abstract: The reactivityo fo rganic photoredox catalysts in oxidation reactions is enhanced by the addition of Lewis acids, which bind to the catalyst to increasei ts oxidizing ability.R edox-inactivem etal ions, such as Sc 3 + ,a lso act as Lewis acids and can bind to flavins to increaset heir oneelectron reduction potentials and photocatalytic stability. The Sc 3 + ion can bind to acridine and pyrene to enhance their photoredox catalytic activity in the oxidation of substrates by dioxygen. The binding of Lewis acids t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 110 publications
0
20
0
Order By: Relevance
“…Subsequently, the luminescence intensity of POM(MoV)-POSS was lower than those of other materials, thus revealing the presence of two different metal sites; this further improved the electron-hole pair separation by inducing electron deficient behavior, which enhanced the photocatalytic hydrogen production activity. 44 To further authenticate photoelectron generation and electron-hole pair separation of POM-POSS hybrid materials, a photocurrent experiment was performed. As clearly seen from Fig.…”
Section: Photoluminescence and Transient Photocurrent Studiesmentioning
confidence: 99%
“…Subsequently, the luminescence intensity of POM(MoV)-POSS was lower than those of other materials, thus revealing the presence of two different metal sites; this further improved the electron-hole pair separation by inducing electron deficient behavior, which enhanced the photocatalytic hydrogen production activity. 44 To further authenticate photoelectron generation and electron-hole pair separation of POM-POSS hybrid materials, a photocurrent experiment was performed. As clearly seen from Fig.…”
Section: Photoluminescence and Transient Photocurrent Studiesmentioning
confidence: 99%
“…Alternatively, the strong binding of Lewis acids to radical counterions inhibits the reverse electron transfer from the radical ions of the substrate to the oxidized photocatalyst, thereby improving the overall photocatalytic activity. [12] The earliest report of the remarkable enhancement of photoredox reaction by Lewis acid metal ions is the photocatalytic oxidation of benzyl alcohol derivatives by dioxygen using flavin and deazaflavin as organic photoredox catalysts. [13] In 1989, Lewis and Barancyk reported that the use of Lewis acids as catalysts enabled the intermolecular [2 + 2] photocycloaddition of coumarins and different olefins.…”
Section: Combining Lewis Acid Catalysis With Photoredox Catalysismentioning
confidence: 99%
“…Lewis [33] and Brønsted acid catalysis in combination with photoredox catalysis has found widespread use due to the ability of such activation modes to impact the redox properties and reactivities of organic substrates. Brønsted acids can dramatically accelerate photo‐reductive processes, enabling proton‐coupled electron transfer (PCET) pathways [34] .…”
Section: Photoredox Organocatalysismentioning
confidence: 99%